PENGARUH KREDIT BERMASALAH DAN PERPUTARAN KAS TERHADAP LIKUIDITAS - Eries Erviana; Noor Shodiq Askandar; Mohammad Amin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study was to determine 1) the effect of non-performing loansand cash turnover on liquidity, 2) the effect of non-performing loans on liquidity, and 3)the effect of cash turnover on liquidity. This study uses a quantitative approach because ituses data in the form of numbers. The population in this study are all Non ForeignExchange National Private Banks registered with Bank Indonesia. The sampling methoduses purposive sampling method, where there are 14 Non Foreign Exchange NationalPrivate Commercial Banks used as the sample studied. Data collection method usesdocumentation method. The analytical tool used is multiple regression analysis.The results show that 1) non performing loans and cash turnoversimultaneously have a significant effect on liquidity, 2) non performing loans have nosignificant effect on liquidity and 3) cash turnover has no significant effect on liquidity.Keywords: non-performing loans, cash turnover, liquidity